2010
DOI: 10.1016/j.progpolymsci.2010.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Polymer nanofibrous structures: Fabrication, biofunctionalization, and cell interactions

Abstract: Extracellular matrix fibers (ECM) such as collagen, elastin, and keratin provide biological and physical support for cell attachment, proliferation, migration, differentiation and ultimately cell fate. Therefore, ECM fibers are an important component in tissue and organ development and regeneration. Meanwhile, polymer nanofibers could play the same critical role in tissue regeneration process. Fibrous structures can be fabricated from a variety of materials and methods with diameters ranging throughout the siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
281
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 446 publications
(316 citation statements)
references
References 234 publications
5
281
0
3
Order By: Relevance
“…In general, hMSCs encapsulated within the hybrid gel adopted a spherical cell morphology, an equilibrium geometry assumed in the absence of microscale features or integrin binding sites, and typical of nanofi brous gels, such as alginate. [ 33 ] Although cells such as chondrocytes and osteoblasts are naturally rounded, [ 34 ] an adherent analogue would benefi t cells with fi broblastic or neuronal morphology and enable methodological fl exibility in printing complex, multiresponsive structures. This could be achieved by introducing cell-binding motifs; for instance, enhanced cell adhesion and spreading has been observed when alginate is covalently tagged with arginylglycylaspartic acid, a tripeptide sequence present in the cellular adhesion protein fi bronectin.…”
Section: Doi: 101002/adhm201600022mentioning
confidence: 99%
“…In general, hMSCs encapsulated within the hybrid gel adopted a spherical cell morphology, an equilibrium geometry assumed in the absence of microscale features or integrin binding sites, and typical of nanofi brous gels, such as alginate. [ 33 ] Although cells such as chondrocytes and osteoblasts are naturally rounded, [ 34 ] an adherent analogue would benefi t cells with fi broblastic or neuronal morphology and enable methodological fl exibility in printing complex, multiresponsive structures. This could be achieved by introducing cell-binding motifs; for instance, enhanced cell adhesion and spreading has been observed when alginate is covalently tagged with arginylglycylaspartic acid, a tripeptide sequence present in the cellular adhesion protein fi bronectin.…”
Section: Doi: 101002/adhm201600022mentioning
confidence: 99%
“…Electrospinning is a versatile production method to produce porous fibers membranes with diameters ranging from few micrometers to several nanometers [7,8]. This process uses a high voltage source to inject charge of a certain polarity into a polymer solution or melt, which is then accelerated, in the form of a thin jet, and when the applied electric field is strong enough to overcome the surface tension of solution the jet is drawn into a fiber that is collected on a surface of a grounded target [9].…”
Section: Introductionmentioning
confidence: 99%
“…The wettability of a polymer surface is then a result of both its surface chemistry and its topography 52 and it has been demonstrated that has a 80 strong influence on cell adhesion and proliferation. Cell morphology is another important characteristic in tissue engineering scaffold design as it allows the control of cell arrangement and the translational effects that cell morphology have on other cell functions 53 . Cell morphology can be 85 influenced by the surface substrate and can adopt different morphologies on fibrous membranes compared to film membranes 54 .…”
mentioning
confidence: 99%